2020
DOI: 10.1016/j.apsusc.2020.146752
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of recrystallization and stress relaxation in nanosecond laser annealed Si1−xGex/Si epilayers

Abstract: 30 nm-thick pseudomorphic Si1-xGex layers with Ge concentrations x ranging from 0 to 0.4 were submitted to Ultraviolet Nanosecond Laser Annealing (UV-NLA). The impact of UV-NLA on the various regimes and on the layer crystallinity was assessed for each Ge concentration. This study highlighted the existence of four annealing regimes, with notably a surface melt regime with isolated molten islands on the surface. The strain in the layer depended on the liquid/solid interface roughness and on the stored elastic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 46 publications
(54 reference statements)
3
20
0
Order By: Relevance
“…In addition, the primary melt starts randomly at the silicon surface (nucleation) as in classical phase transitions [30,31]. For a laser pulse duration of 145 ns, it has been shown that melt droplets as thick as ~15 nm can be formed at the onset of surface melt while adjacent areas can be melted down to a lower depth or even remain in the solid phase [32]. In our case, due to the difference in melting temperature between a-Si and c-Si [27], the maximum thickness of the melted droplets in the surface melt regime might well correspond to the thickness of the entire a-Si layer.…”
Section: Fig 2 (A) Hrem Images Of the As-implanted Sample; (B) Trr Si...mentioning
confidence: 99%
“…In addition, the primary melt starts randomly at the silicon surface (nucleation) as in classical phase transitions [30,31]. For a laser pulse duration of 145 ns, it has been shown that melt droplets as thick as ~15 nm can be formed at the onset of surface melt while adjacent areas can be melted down to a lower depth or even remain in the solid phase [32]. In our case, due to the difference in melting temperature between a-Si and c-Si [27], the maximum thickness of the melted droplets in the surface melt regime might well correspond to the thickness of the entire a-Si layer.…”
Section: Fig 2 (A) Hrem Images Of the As-implanted Sample; (B) Trr Si...mentioning
confidence: 99%
“…Moreover, stacking faults starting from the initial amorphous/crystalline (a/c) interface can be observed even at such a full melt condition [43]. They might come either from possible nonuniformity of the as-implanted a/c interface or from nonuniform l/s interface during UV-LA [55,56].…”
Section: Dopant Activation By Liquid Phase Epitaxial Regrowth (Lper)mentioning
confidence: 99%
“…Therefore, after pulsed laser annealing, initially uniform SiGe thin films transform into compositionally graded thin films with a high Ge concentration on the top surface. [133][134][135] Moreover, the depth of the melted SiGe film and the Ge concentration at the top surface can be controlled by the laser fluence. This is quite appealing for applications such as contact resistance lowering in doped SiGe films, and the formation of graded SiGe buffer layers for epitaxial growth of group III-V semiconductor-based photonic devices.…”
Section: Laser-driven Phase Segregation In Sige Alloy Thin Films With Uniform Compositionmentioning
confidence: 99%